L-NG-nitro arginine methyl ester exhibits antinociceptive activity in the mouse. - Moore, P. K. (1991)
1. L-NG-nitro arginine methyl ester (L-NAME, 1-75 mg kg-1) administered intraperitoneally (i.p.) elicits dose-related antinociception in the mouse assessed by the formalin-induced paw licking procedure. Antinociceptive activity is still present 24 h after injection. L-NAME (75 mg kg-1, i.p.) is also antinociceptive in the acetic acid-induced abdominal constriction and hot plate procedures. 2. L-NAME additionally produces a dose-related inhibition of formalin-induced paw licking following intracerebroventricular (i.c.v., 0.1-100 microgram per mouse) and oral (p.o., 75-150 mg kg-1) administration. 3. L-Arginine (600 mg kg-1, i.p.) but not D-arginine (600 mg kg-1) or naloxone (5 mg kg-1) reverses the antinociceptive effect of L-NAME in the formalin test. 4. High doses of L-NAME (37.5-600 mg kg-1) but not D-NAME (75 mg kg-1) administered i.p. produce dose-related increases in blood pressure of the urethane-anaesthetized mouse whilst i.c.v. injected L-NAME (0.1 and 100 microgram per mouse) in inactive. 5. L-NAME (75 mg kg-1, i.p.) did not inhibit oedema formation in the formalin-injected mouse hindpaw. 6. L-NAME (75 mg kg-1) did not produce any overt behavioural changes in treated mice and failed to influence locomotor activity or the incidence of dipping, crossing, rearing or circling behaviour assessed by a modified 'head-dipping' board procedure. A high dose of L-NAME (600 mg kg-1) reduced dipping behaviour and locomotor activity suggesting a possible sedative effect.(ABSTRACT TRUNCATED AT 250 WORDS)